Frailty and associated risk factors in patients with Sjögren’s disease: a cross-sectional study - Tian, Zhen; Liao, Qiuju; Wang, Chunxiu; Wang, Leiming; Chhetri, Jagadish K.; Zhao, Yi; Chan, Piu (Frontiers in Immunology, 2025)
IntroductionThis study aimed to evaluate the prevalence of frailty and to identify its associated risk factors in hospitalized patients with Sjögren’s disease (SjD).MethodsA cross-sectional study was conducted among hospitalized SjD patients at Xuanwu Hospital between August 2022 and October 2024. Frailty was evaluated using the Fried Frailty Phenotype, which comprises five components: unintentional weight loss, self-reported exhaustion, low physical activity, slowness, and weakness. Based on established criteria, patients were categorized as frail (≥3 criteria), pre-frail (1–2 criteria), or robust (0 criteria).ResultsA total of 180 patients were included in the final analysis. The prevalence of frailty and pre-frailty was 27% and 49%, respectively. Multivariate logistic regression analyses identified higher c-reactive protein (OR = 1.080, 95% CI: 1.020-1.144, P = 0.008), the EULAR Sjögren’s Syndrome Disease Activity Index (OR = 1.082, 95% CI: 1.027-1.140, P = 0.003), and EULAR Sjögren’s Syndrome Patient Reported Index (OR = 1.271, 95% CI: 1.064-1.518, P = 0.008) as independent risk factors for frailty.ConclusionsFrailty is commonly observed among hospitalized patients with SjD and is independently associated with systemic inflammation and disease activity. These findings underscore the need for routine frailty assessment in clinical practice, particularly among patients with elevated inflammatory markers and more severe disease manifestations.